CASE REPORT: USE OF INTRAPERITONEAL CEFTRIAXONE IN THE PREVENTION OF PERITONITIS IN A MARE WITH RUPTURED RECTUM - Mendes, Lívia Rodrigues; Fonseca, Maria Cecilia Silva; Alves, Nysa Neves; Costa, Fabiane de Paula Carvalho; Gusmão, Emerson Márcio; da Silva, Matheus Pereira; Araújo, Amanda Cunha; da Costa, Maria Dulcinéia; Lopes, Maria Eduarda Ramalho; Siqueira, Juliano Santos; Costa, Renê Ferreira; Pires Neto, Otaviano de Souza; et al. (Seven Editora, 2025)
This report describes the treatment of a two-year-and-seven-month-old Quarter Horse mare diagnosed with grade III rectal rupture after reproductive manipulation. The initial approach suggested corrective surgery with a colostomy, but the owner's refusal led the team to conservative treatment. The protocol included fluid therapy, analgesia, systemic support, and antibiotic administration, with emphasis on the introduction of ceftriaxone intraperitoneally at a dose of 50 mg/kg/day for five days to prevent the onset of septic peritonitis. The treatment was well tolerated and resulted in significant clinical improvement, with recovery of intestinal motility, hematologic normalization, and clinical stabilization. The adopted approach, although alternative, proved effective, with ceftriaxone being a promising resource for controlling abdominal infections in severe non-surgical cases.DOI: https://doi.org/10.56238/sevened2025.029-097